2022
DOI: 10.7759/cureus.30886
|View full text |Cite
|
Sign up to set email alerts
|

Perks of Early Physical Therapy Rehabilitation for a Patient With Diffuse Axonal Injury

Abstract: Traumatic brain injury (TBI) is characterized as any neurological trauma that develops after birth and therefore is completely unconnected from congenital anomalies, developmental disorders, or gradual processes. People who have survived accidents or other severe head injuries that left them with brain damage have been linked to memory loss and disability. On February 9, 2022, a 23-year-old individual was taken to a nearby hospital with a head injury after being involved in a traffic accident that morning whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They, however recommended further studies with larger sample to draw adequate conclusions on the role of early neurorehabilitation in TBI outcome. Furthermore, a case study in India was reported by Lalwani et al [ 29 ] on a 23-year-old man who sustained a TBI (diffuse axonal injury), he received rehabilitation at three levels: (i) in the neurosurgery ICU (guidance and counselling of family members, manual positioning in 2 h intervals, manual chest vibrations and percussion, chest proprioceptive neuromuscular facilitation (PNF), end-expiratory pressure, facilitating technique like quick icing and quick stretch); (ii) in the neurosurgery ward (thoracic expansion exercises, bilateral active range of motion exercises both upper and lower limbs, isometric exercises for quadriceps and hamstrings, stretching, out of bed mobilization with wheelchair); and (iii) physiotherapy rehab (functional electric stimulation, more strengthening for the limbs and trunk muscles, verticalization with tilt tables, coordination exercises, gait re-education). They concluded that the TBI survival had a remarkable progress in the physical and functional health of the patient.…”
Section: Rehabilitation and Its Importance In Overall Tbi Carementioning
confidence: 99%
“…They, however recommended further studies with larger sample to draw adequate conclusions on the role of early neurorehabilitation in TBI outcome. Furthermore, a case study in India was reported by Lalwani et al [ 29 ] on a 23-year-old man who sustained a TBI (diffuse axonal injury), he received rehabilitation at three levels: (i) in the neurosurgery ICU (guidance and counselling of family members, manual positioning in 2 h intervals, manual chest vibrations and percussion, chest proprioceptive neuromuscular facilitation (PNF), end-expiratory pressure, facilitating technique like quick icing and quick stretch); (ii) in the neurosurgery ward (thoracic expansion exercises, bilateral active range of motion exercises both upper and lower limbs, isometric exercises for quadriceps and hamstrings, stretching, out of bed mobilization with wheelchair); and (iii) physiotherapy rehab (functional electric stimulation, more strengthening for the limbs and trunk muscles, verticalization with tilt tables, coordination exercises, gait re-education). They concluded that the TBI survival had a remarkable progress in the physical and functional health of the patient.…”
Section: Rehabilitation and Its Importance In Overall Tbi Carementioning
confidence: 99%
“…The major goals of therapy are frequently muscular improvement, prevention of subsequent injury such as pneumonia or stiffness, and recovery of consciousness and sensorimotor viewpoint. The primary goal is to get the maximum degree of movement and self-care capability [ 11 ].…”
Section: Introductionmentioning
confidence: 99%